Приключения Одиссея - Тудоровская Елена Александровна (Школьная библиотека, 2001)
Экземпляры: ф.23 (2003) / Инвентарный номер: 47157 / Цена: / Сис.шифр: 82.3(0)-6 / Авт.знак: П 75 / ГРНТИ: 17.71.91 / ББК: 82.3(0)-6